How are Acne Vulgaris Patients Using Oral Isotretinoin Affected by COVID-19? - Mine Müjde Kuş; Perihan Öztürk; Tutku Bulut; Celal Kuş; Mehmet Enes Güner; Hülya Nazik; Mehmet Kamil Mülayim (Mattioli1885, 2022)
Introduction: It has been reported that the use of oral isotretinoin may have positive and negative effects on the course of COVID-19 and the risk of transmission. Objectives: The purpose of our study is to evaluate how our patients that took oral isotretinoin during the pandemic were affected by COVID-19. Methods: The clinical processes of moderate-to-severe acne vulgaris patients between March 2020 and February 2021 were evaluated. Results: Of 102 moderate-to-severe acne patients, 67 were using oral isotretinoin and 35 were using a topical treatment. Of 27 patients who tested positive for COVID-19, 16 (59.3%) were using oral isotretinoin and 11(40.7%) were using topical treatment, there was no statistical difference in the rates of COVID-19 positivity between the two groups (P = 0.412). The rates of positive tests for COVID-19 were similar between contacted patients of two groups (P = 0.391). Loss of smell/taste was lower in patients using oral isotretinoin compared to patients receiving topical treatment (46.7% and 72.7%, respectively.). Headache symptoms were less common in patients using oral isotretinoin (P = 0.047). Conclusions: The use of oral isotretinoin did not cause an increase or decrease in the risk of COVID-19 transmission. The patients using oral isotretinoin had a lower incidence of taste/smell loss and headache.